The Legality of Doctrine of Frustration in the Realm of Covid-19 Pandemic - Sheela Jayabalan (Sociological Jurisprudence Journal, 2020)
The outbreak of the novel coronavirus (â€œCOVID-19-Outbreakâ€) has a potential impact in the performance of a contract. If a contract does not contain a force majeure clause, a contracting party may look to the common law doctrine of frustration to relieve it from its obligations. Unlike force majeure clauses which focuses on the parties' express intention on how to deal with supervening events, frustration is implied by law and thus would only be considered in the absence of an express force majeure clause. In Malaysia, the doctrine of frustration is codified in section 57(2) of the Contracts Act 1957. A doctrinal analogy of the doctrine of frustration and section 57 of the Contracts Act 1950 indicates a pandemic such as the covid-19 would not frustrate a contract. Force majeure clause should be used as a protective tool to prevent losses to the contracting parties or alternatively the Principles of European Contract Law and the Unidroit Principles that make provisions for hardship as well as force majeure should be implemented.